Clinical picture of the amyloid arthropathy in patients with chronic renal failure maintained on haemodialysis using cellulose membranes. - Muñoz-Gómez, J (1987)
The clinical picture of 15 patients (10 male, five female) with amyloid arthropathy secondary to chronic renal failure treated with haemodialysis has been studied. The average period of haemodialysis was 10.8 years. Joint symptoms appeared between three and 13 years after starting haemodialysis. No patient had renal amyloidosis. Early symptoms were varied and often overlapped: knee swelling (seven patients), painful and stiff shoulders (seven), and carpal tunnel syndrome (six) were the most prominent. Follow up showed extension to other joints. Joint effusions were generally of the non-inflammatory type. Radiologically, geodes and erosions of variable sizes were seen in the affected joints, which can develop into a destructive arthropathy. Amyloid was found in abdominal fat in three of the 12 patients on whom a needle aspiration was performed. Four of 12 patients showed changes compatible with amyloid infiltration in the echocardiogram. One patient had amyloid in the gastric muscular layer, another in the colon mucus, and two of four in rectal biopsy specimens. Amyloid deposits showed the presence of beta 2 microglobulin in 10 patients. The clinical and radiological picture was similar to the amyloid arthropathy associated with multiple myeloma. These patients can develop systemic amyloidosis.